Energy harvesting for IoT sensor systems - Lai, Wen Pang (Nanyang Technological University, 2020)
This project aims to assist businesses that offer a full spectrum of customised gateway services to their clients, ranging from logistics to industrial catering as well as manufacturing. Currently, businesses are using conventional methods like the dolly trolley to transport their items regardless of the size of items. This creates an issue of large deployments of dolly trolleys, thus making it hard to track the individual location of each dolly trolley. A simple solution will be to attach a Global Positioning System (GPS) on the trolleys that will allow tracking. Furthermore, the system needs to be durable and can allow easy maintenance. The industrial assets that require monitoring are located outside of the factory settings and are not connected to any power source, hence arises the issue of powering up the sensor systems. Furthermore, these devices are located outdoors and will be exposed to the weather environment. This project will focus on the design and prototype of a kinetic based harvesting system, that powers up a GPS that has a lifespan of at least a few years and is durable enough to survive extreme weather conditions. Once the hardware is created, it will be implemented on the trolleys, which will solve the issues of tracking the trolley. Hardware implementation and embedded software programming will be included in this project.